Development of microweir structure by lithographic fabrication process for malaria cell separation - Sivaraj, Lalitha (2016)
Malaria, a mosquito-borne deadly disease invades millions of lives yearly and consumes the socio and economic resources for drug invention and treatment. Besides early disease detection is hampered by limited resources and unavailability of portable detection system in rural areas. Hence the present work concentrates on improving the available impedance based malaria detection system through red cell separation. To maximise the detection efficiency narrow microchannels are designed to suit the dimension of a single red blood cell (RBC) which demands white blood cell (WBC) separation. RBC separation is achieved in the present work using the passive and crossflow filtration by microweir components. It works based on the principle of laminar flow under different pressure gradients, creating the necessary suction force to drag the red cell to the appropriate location. It offers the benefits of easy fabrication, reproducibility and good cell separation with unaltered cell property. Therefore the development of microweir structure for malaria cell separation is been studied in this work to understand its efficiency and limitations. The key parameters influencing weir separation efficiency are including flow rate, channel length and channel width are derived through the numerical study. They are then optimized through simulation made on three dimensional models built in Comsol Multiphysics software. The simulation results are analysed using Anova test to find the significance among the different values being simulated for each parameter. Later the microweir separation chip is fabricated through the traditional ultraviolet (UV) lithographic process on the positive photoresist AZ1518. The experiment on separation is made on beads of sizes 2, 3 and 5 μm at three different flow rate values of 0.03ml/hr, 0.05 ml/hr and 0.07 ml/hr. The simulation results showed the buffer flow rate reduced to a tenth of particle flow rate, side channel length of 100 μm and side channel width of 40 μm produced higher bead count value at the secondary channel while reducing the value at primary channel. The simulation of different weir height could not be effectively analysed due to the limitations of the chosen study physics and simulation software used. The experiment and simulation results are then analysed using imageJ image processing software to calculate the bead count and velocity magnitude. The experiment result shows an efficient separation of 5 μm beads from the 2 μm and 3 μm beads qualitatively. The analysis of bead count at the secondary channel shows 45.6%, 34.2% and 16.7% separation efficiency and 113 μm/s, 168 μm/s and 350 μm/s as the average bead velocity at 0.03 ml/hr, 0.05ml/hr and 0.07 ml/hr respectively. Later the simulation bead count and velocity is compared with experimental result by running T-test on SPSS statistical software. The results show a P < 0.05, implying no significant differences between the experiment and simulation results.